2012
DOI: 10.1002/art.33379
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of anti‐p155 autoantibody for diagnosing cancer‐associated dermatomyositis: A systematic review and meta‐analysis

Abstract: Objective. Anti-p155 autoantibody, which was recently described in adult patients with dermatomyositis (DM), seems to be associated with cancer in this population. We performed a systematic review and metaanalysis to ascertain the accuracy of anti-p155 testing for the diagnosis of cancer-associated myositis.Methods. We searched relevant databases, with no restrictions on study design or language, for original studies that included adult patients with probable/ definite DM or amyopathic DM who were evaluated fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
202
5
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(226 citation statements)
references
References 53 publications
9
202
5
10
Order By: Relevance
“…Ryzyko to zostało dokładniej ocenione przez Trallero-Araguasa i wsp. [38] w metaanalizie dotyczącej 6 badań kohortowych, uwzględniającej łącznie dane 312 chorych z DM. Opisywane przeciwciała cechuje 89-procentowa swoistość i 78-procentowa czułość dla stwierdzenia nowotworu, z dodatnią wartością predykcyjną wynoszącą 58%, a ujemną wartością predykcyjną -aż 95%.…”
Section: Przeciwciała Anty-mda5 (Anty-cadm-140)unclassified
“…Ryzyko to zostało dokładniej ocenione przez Trallero-Araguasa i wsp. [38] w metaanalizie dotyczącej 6 badań kohortowych, uwzględniającej łącznie dane 312 chorych z DM. Opisywane przeciwciała cechuje 89-procentowa swoistość i 78-procentowa czułość dla stwierdzenia nowotworu, z dodatnią wartością predykcyjną wynoszącą 58%, a ujemną wartością predykcyjną -aż 95%.…”
Section: Przeciwciała Anty-mda5 (Anty-cadm-140)unclassified
“…We read with great interest the recent systematic review and meta-analysis by Trallero-Araguás et al on the relationship between the anti-p155 autoantibody and cancerassociated myositis (1). By using the pooled sensitivity and specificity of the selected 6 studies, the authors concluded that the diagnostic odds ratio (OR) for anti-p155 was 27.26 (95% confidence interval [95% CI] 6.59-112.82), the positive likelihood ratio was 6.79 (95% CI 4.11-11.23), and the negative likelihood ratio was 0.25 (95% CI 0.08-0.76).…”
Section: To the Editormentioning
confidence: 99%
“…These include antibodies against PL7, PL12, OJ, EJ, KS, Ha, Zo Anti-Mi2 antibodies [Targoff and Reichlin, 1985] These have been described over 25 years ago and have been linked with classic dermatomyositis rashes. There may be a link with ultraviolet irradiation in their development Anti-p155/140 (TIF1-γ) [Trallero-Araguás et al 2012;Muro et al 2012;Saroh et al 2012] These antibodies were first described in 2006/2007. They are linked with cancer-associated myositis.…”
Section: Antibody and References Detailsmentioning
confidence: 99%